Stimulatory effects of ghrelin on spontaneous contractions in the rat myometrium - Dayangac, Alpaslan; Kutlu, Selim; Konar, Vahit (Tubitak Scientific & Technological Research Council Turkey, 2010)
Ghrelin, a recently isolated hormone, has been reported to have modulatory effects on smooth muscle contractility. In this study, we investigated the effects of ghrelin on spontaneous contractions in the rat uterus in vitro. Myometrium strips were removed from Wistar rats following decapitation and placed in a jacketed tissue bath. After initiation of spontaneous contractions, control contractions were recorded for 10 min and various concentrations of ghrelin were added to the tissue bath cumulatively. The Wilcoxon signed ranks test was used for statistical analysis. Application of ghrelin augmented the spontaneous contractions in myometrial strips. The mean peak amplitudes of contractions were 2.69 +/- 0.32 g (n = 6), 2.71 +/- 0.31 g (n = 6), 2.92 +/- 0.36 g (n = 6), and 3.46 +/- 0.24 g (n = 6) under control conditions and after application of 0.01 mu M, 0.1 mu M, and 1 mu M ghrelin, respectively. The mean frequencies of contractions were 5.17 +/- 0.75 (n = 6), 5.17 +/- 0.75 (n = 6), 5.33 +/- 0.48 (n = 6), and 8.0 +/- 0.77 (n = 6) under control conditions and after application of 0.01 mu M, 0.1 mu M, and 1 mu M ghrelin, respectively. The increase in amplitude and frequency of contractions was significant only after application of 1 mu M ghrelin (P < 0.05). Data from this study demonstrated that ghrelin induces spontaneous contractions in a dose-dependent manner in the rat myometrium.
Ghrelin'in siçan miyometriyumundaki spontan kasilmalara uyarici etkileri
Keywords: Ghrelin; spontaneous contractions; myometrium; rat